Genomic analysis of the main epidemiological lineages of Acinetobacter baumannii in Mexico - Humberto, Barrios-Camacho; Luis, Lozano-Aguirre; Josefina, Duran-Bedolla (Frontiers in Cellular and Infection Microbiology, 2025)
Acinetobacter baumannii has emerged as a critical global health threat due to its exceptional survival skills in adverse environment and its ability to acquire antibiotic resistance, presenting significant challenges for infection treatment and control. The World Health Organization has classified carbapenem-resistant A. baumannii as a “Critical Priority” pathogen to guide research and the development of control and prevention strategies. Epidemiological surveillance methodologies provide the tools necessary for classifying A. baumannii into international clonal lineages, facilitating the analysis of molecular characteristics, global dissemination, and evolution. This study provides a detailed analysis of the molecular epidemiology of A. baumannii in Mexico, focusing on identifying the main international clonal lineages. Genomic analyses of 146 genomes, along with information from previous studies, identified 24 different sequence types according to the Oxford Scheme. The major international clone IC2 (CC208) was identified and harbors β-lactamases OXA-66, ADC-30, OXA-72, and is predicted to possess the OCL1 locus. The international clone IC5 (CC205) carries β-lactamase OXA-65, along with ADC-214 and OXA-239, with OCL10 predicted in 82.2% of the genomes. The international clone IC7 (CC229) harbors β-lactamase OXA-64, as well as ADC-174 and ADC-214, with OCL6 and OCL7 loci predicted. These international clones were identified in different periods and regions of Mexico and are likely to be widely distributed throughout the country. The analysis of each lineage reveals distinct molecular characteristics, including sequence types, capsule typing, outer core loci, and specific antibiotic resistance profiles. Understanding these features is crucial for elucidating their roles in infection dynamics, resistance mechanisms, and their impact on clinical outcomes.